Ensino e aprendizagem nos livros didáticos de história (1960/2000) : que concepções apontam os exercícios? - Moura, Ana Maria Garcia (2011)
This research analyzes the exercises from History textbooks which came out between the periods of 1960 to 2000 and it was destined for age group of 10 to 17. Its mainly objective was: identifying the changes and the permanencies in the conceptions of teaching and learning. The analysis considered the following indicators: solicited actions, involved individuals, object of the exercise, localization, teacher role. The exercise was considered to be such a technic which sought to drill, to improve specific capacities and abilities, as a way to effecting and conferring the learning. With the exam, it was searched the evidences of a pedagogics theories trajectory in the textbook and the aspects of the teaching History. The prominence of this study is the approach made on this important source to the historical learning, the exercise, and in the vestiges which indicate on the ways how the textbooks assume the several existent perspectives about the teaching and learning process.